2020
DOI: 10.1111/aman.13411
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the Present: Archaeology in 2019

Abstract: Postmodernity has a distinctly pre‐apocalyptic feel to it, and this feeling has seeped into archaeology. A review of the scholarship from 2019 attests that archaeologists are having to reckon with present‐day conditions and phenomena as they structure their research, delineate the material world, and affirm archaeology's relevance. Furthermore, these concerns have moved from the realm of the rarely spoken and come to constitute a critical conversation in the field. In a number of respects, the contours of arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 176 publications
(173 reference statements)
0
13
0
Order By: Relevance
“…A review of mission and policy statements of archaeological professional organisations, heritage agencies and university departments, including the Chartered Institute for Archaeologists' recently published information sheet on Delivering Public Benefit from Archaeology [12] readily evidences a sense of self-conscious awareness of archaeological practitioners' responsibility for public value. This active foregrounding of archaeology's relevance to contemporary society's needs, its social impacts, and potential for wider public and environmental benefit is likewise reflected in, and simultaneously promoted by, a growing body of critically reflective scholarship which explicitly discusses archaeology's wider context, e.g., [13][14][15][16][17][18]. This positioning is furthered through the close links between archaeology and heritage, which directly wire the presentation of archaeological evidence, interpretations, and ideas into contemporary issues of identity politics, power, ownership and sustainability.…”
Section: Intellectual and Social Context Of The Workmentioning
confidence: 99%
“…A review of mission and policy statements of archaeological professional organisations, heritage agencies and university departments, including the Chartered Institute for Archaeologists' recently published information sheet on Delivering Public Benefit from Archaeology [12] readily evidences a sense of self-conscious awareness of archaeological practitioners' responsibility for public value. This active foregrounding of archaeology's relevance to contemporary society's needs, its social impacts, and potential for wider public and environmental benefit is likewise reflected in, and simultaneously promoted by, a growing body of critically reflective scholarship which explicitly discusses archaeology's wider context, e.g., [13][14][15][16][17][18]. This positioning is furthered through the close links between archaeology and heritage, which directly wire the presentation of archaeological evidence, interpretations, and ideas into contemporary issues of identity politics, power, ownership and sustainability.…”
Section: Intellectual and Social Context Of The Workmentioning
confidence: 99%
“…Archaeologies of the contemporary past have increasingly used traditional archaeological methods to supplement sociological, geographical and political analyses of the last half of the twentieth and early twenty-first centuries (Buchli and Lucas 2001;Graves-Brown et al 2013;Ferris et al 2014), and theoretical archaeology is now often made relevant to socio-material practices, acknowledging the inherent multi-temporality of these investigative contributions (Harrison and Breithoff 2017). Other recent scholarship in the field has demonstrated that, following a focus on contemporary society, certain scholars of the past can and do address issues in the present, such as capitalism, neoliberalism, inequality, climate change, food insecurity, racism, xenophobia and neocolonialism (Rosenzweig 2020). In museology, these theories have been explored by the late Fernando Estévez González.…”
Section: The Politics Of Latin American Archaeology In the Museummentioning
confidence: 99%
“…Archaeology can amplify this knowledge by raising up the voices of Black archaeologists and communities whose heritages are involved (e.g., Epperson 2004; Franklin 1997), following the #BlackLivesMatter movement and its intersections with archaeology (see also Rosenzweig 2020). A virtual panel on June 26, 2020, “Archaeology in the Time of Black Lives Matter,” drove home this point with six panelists (Justin Dunnavant, Ayana Flewellen, Maria Franklin, Alexandra Jones, Alicia Odewale, and Tsonie Wolde-Michael) and more than 1,600 online attendees.…”
Section: Epidemic Disease Among Indigenous Peoples Black Communitiesmentioning
confidence: 99%